The Influence of the STAD and PowerPoint-Assisted Jigsaw Models on Economics Learning Achievement - I Gusti Putu Endra Suantara; Albert Amartey; Joel P Kankani (Journal of Social Knowledge Education (JSKE), 2023)
Purpose of the study: The aim of this research is to determine the effect of cooperative learning models such as Student Teams Achievement Divisions (STAD) and Jigsaw with the help of PowerPoint media on Economics learning achievement. Methodology:This research is quantitative research with experimental methods. The sampling technique is simple random sampling. The sample in this study was 70 students. Data collection techniques in this research are questionnaires. The data analysis technique in this research uses two-way analysis of variance with an unequal number of cells with analysis prerequisite tests, namely the normality test and homogeneity test. Main Findings: The results of the research show that there are differences in the influence of the Student Teams Achievement Divisions (STAD) and Jigsaw cooperative learning models assisted by PowerPoint media on Economics learning achievement. This is shown by obtaining a significance value (Sig.) which is smaller than the significance level α = 0.05, namely (0.00 < 0.05) or (Fobs = 10.103 >Ftable = 4.00). Novelty/Originality of this study: The novelty of this research is that it contributes to the study and development of knowledge, especially regarding cooperative learning approaches such as Student Teams Achievement Divisions (STAD) and Jigsaw.